ChemInform Abstract: Critical Surveys Covering the Year 2011: Organometallic Compounds in Organic Synthesis. Issue 42 (1st October 2013) - Perna, Filippo Maria; Solomone, Antonio; Capriati, Vito
Abstract Review: new applications of organometallics as catalysts or reagents in organic syntheis; 108 refs.